Electronic Word of Mouth, Perceived Price, and Brand Image Increasing Purchase Intention in RedDoorz Indonesia Through Perceived Service Quality as Intervening Variable - Etty Nurwati; Pamuji Gesang Raharjo; Nurma Yuliani (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
To analyze the direct and indirect effects of electronic word of mouth, perceived price,brand image, perceived service quality, and purchase intention variables. Theresearch was conducted on users of the RedDoorz Application in Indonesia.Collecting data with instruments that have been tested for validity and reliability, bya questionnaire distributed via google form using accidental sampling technique. Atotal of 330 samples were collected, the data was processed by SEM using SmartPLS3.2.9. There is a significant positive effect of Electronic Word of Mouth, PerceivedPrice, Brand Image on Perceived Service Quality, and Purchase Intention. The variablethat has the most direct influence on Purchase Intention is Perceived Price, and theindirect influence through perceived service quality is Brand Image.